Lietuviška knyga pirmojo pasaulinio karo metais - Stonienė, Vanda (Knygotyra, 1992)
The development of Lithuanian book publishing was severely hampered during the World War I. In 1915 Lithuania was occupied by Germany military forces and no activities of cultural institutions were allowed without a permission of the occupants. A single newspaper (“Dabartis”) was being published from 1915 on by them. Besides, Catholic society was permitted later to have its periodic edition “Ateitis”. Only at the beginning of 1918, under the threat of complete failure of their colonial plans, the occupants allowed publishing Lithuanian newspapers “Lietuvos aidas”, “Tėvynės sargas”, “Darbo balsas”, etc.Military occupation regime, every-day life difficulties, hard censorship exerted an extremely negative influence on publishing Lithuanian books. Every edition needed an official permission of German military power. Therefore, text-books, annual almanacs, small popular science editions could mostly be issued. Publication work was being performed by Lithuanian Scientific Society, St. Casimir’s Society, M. Šlapelienė bookshop. The demand for books among the population of Lithuania was great but it was impossible to satisfy it. In addition, the occupants closed almost all big libraries, even the transport of books was banned completely.In 1915, under the conditions of approaching front-line, about 300.000 inhabitants and many institutions were forced to withdraw from Lithuania. In St. Petersburg, Moscow, Woronezh and other Russian cities large colonies of Lithuanian refugees were formed. They were mostly supported by the Lithuanian Society of War Refugees. The society established in St. Petersburg its newspaper “Lietuvių balsas”, founded some schools for Lithuanian pupils, organized training courses, for adults; several text-books and other books were issued by it. During the war period the society has published about 50 Lithuanian editions. Other charity societies also have organized some editions.In 1918 Lithuanian refugees began returning to their motherland. The Lithuanian Society of War Refugees continued its activities until February 1918, when its cultural work was banned by the Soviet power.